ESTIMASI POPULASI TANGKASI (Tarsius wallacei Merker et al., 2010) DI DESA LEBANU KECAMATAN MARAWOLA KABUPATEN SIGI PROVINSI SULAWESI TENGAH - Chalvin Rio Bethony; Annawaty Annawaty; Yulius Duma (Biology Department, Mathematics and natural science, Tadulako University, 2017)
Sulawesi is an island that has high biodiversity. However, utilization of natural resources has been harming habitat of animals. The destructions of their habitat cause some animals become extinct from earth. Tarsius wallacei is one of the primate species from Tarsidae family and is an endemic species of Central Sulawesi region. This research was done because the status of Tarsius becomes an endangered species. The purpose of this research was to estimate the population of T. wallacei at Lebanu village. This research was conducted during 3 months using Point Count method. The result of this research showed that populations of T. wallacei at Lebanu village are 11 groups and their densities are 0.19 groups/ha.